Compositional analysis of the essential oil of Boswellia dalzielii frankincense from West Africa reveals two major chemotypes. (August 2019) - DeCarlo, Anjanette; Johnson, Stephen; Okeke-Agulu, Kingsley I.; Dosoky, Noura S.; Wax, Sophia J.; Owolabi, Moses S.; Setzer, William N.
Abstract: Frankincense, an oleoresin produced by Boswellia species, has historical medicinal and religious significance, and is today used extensively for its essential oil. Boswellia dalzielii, a species found in West Africa, is one of the few frankincense species for which there is no information on the oleoresin essential oil. In order to correct this deficiency, the chemical compositions of the essential oil hydrodistilled from 21 samples of oleoresin taken directly from B. dalzielii trees in northern Nigeria, were analyzed by gas chromatography – mass spectrometry as well as chiral gas chromatography. In addition, a hierarchical cluster analysis was performed on the essential oil compositions from the 21 oleoresin samples from northern Nigeria as well as two samples from Ghana. The essential oil fractions obtained by hydrodistillation of B. dalzielii oleoresins were dominated by α-pinene (21.7–76.6%), followed by α-thujene (2.0–17.6%), myrcene (up to 35.2%), p -cymene (0.3–15.6%), and limonene (1.1–32.9%). The levorotatory enantiomers predominated for the monoterpenes with 98.1 ± 1.5% (−)-α-thujene, 99.2 ± 0.5% (−)-α-pinene, and 96.8 ± 1.4% (−)-β-pinene. Limonene showed the largest variation in enantiomeric distribution [67.3 ± 12.1% (−)-limonene]. The cluster analysis revealed two major chemotypes, one dominated by α-pinene and one much rarer chemotype rich in myrcene. Graphical abstract: Image 1 Highlights: Essential oils have been collected from 21 Boswellia dalzielii trees from northern Nigeria. Boswellia dalzielii resin oils were dominated by α-pinene, α-thujene, myrcene, or limonene. The levorotatory enantiomers predominated for the monoterpenes. Cluster analysis revealed two chemotypes: α-Pinene and myrcene.